Handgrip strength in older adults and driving aptitude - Maria Helena Lenardt; Tânia Maria Lourenço; Susanne Elero Betiolli; Maria Angélica Binotto; Clarice Maria Sétlik; Márcia Marrocos Aristides Barbiero (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to analyze handgrip strength as a predictor of the inability to drive in older adults. Method: a cross-sectional study conducted in traffic clinics with 421 older adults in Curitiba-Paraná from January 2015 to December 2018. A sociodemographic and clinical questionnaire, handgrip strength test, and queries from the National Registry of Qualified Drivers form were applied. Results: Reduced handgrip strength was not a predictor of inaptitude for vehicular driving (p=0.649). The predictors of inaptitude were: low education (p=0.011), incomplete elementary education (p=0.027), and cognition (p=0.020). Conclusion: reduced handgrip strength was not shown to predict for loss of driving skills in older adults. Low education level and reduced cognition level are conditions that were shown to be predictors for loss of vehicular driving license.